1985
DOI: 10.1161/01.atv.5.5.481
|View full text |Cite
|
Sign up to set email alerts
|

Effects of two forms of hypertension on atherosclerosis in the hyperlipidemic baboon.

Abstract: We examined the relationship of hypertension and plasma renin activity to atherogenesis in 48 moderately hyperlipidemic (total serum cholesterol was about 200 mg/dl) baboons (Papio sp.). We used renal artery stenosis (two-kidney, one clip model) to produce hypertension associated with elevated plasma renin activity, and used cellophane wrapping of both kidneys (bilateral perinephritis model) to produce hypertension with normal renin activity. Renal artery stenosis and bilateral perinephritis increased both sys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
18
0

Year Published

1989
1989
2009
2009

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 59 publications
(19 citation statements)
references
References 42 publications
1
18
0
Order By: Relevance
“…exacerbates atherosclerosis in the hyperlipidemic animals. 32,33 Clinical studies have shown that hypertension is associated with increased intima-media thickness and more frequent plaques in extracoronary arteries, more frequent calcifications in coronary arteries, increased wall rigidity in the aorta and peripheral arteries, and impaired endotheliumdependent vasodilation and abnormal blood rheology, which are capable of promoting thrombosis in the background of atherosclerosis. 34 Our finding that 7.5-month-old, but not 6-week-old, Apoe -/-mice exhibited increased arterial pressure is basically consistent with an earlier report demonstrating only a modest increase in blood pressure measured by a tail-cuff method in either restrained or anesthetized mice at 9 weeks of age compared with the controls, which was not statistically significant.…”
Section: Apoementioning
confidence: 99%
“…exacerbates atherosclerosis in the hyperlipidemic animals. 32,33 Clinical studies have shown that hypertension is associated with increased intima-media thickness and more frequent plaques in extracoronary arteries, more frequent calcifications in coronary arteries, increased wall rigidity in the aorta and peripheral arteries, and impaired endotheliumdependent vasodilation and abnormal blood rheology, which are capable of promoting thrombosis in the background of atherosclerosis. 34 Our finding that 7.5-month-old, but not 6-week-old, Apoe -/-mice exhibited increased arterial pressure is basically consistent with an earlier report demonstrating only a modest increase in blood pressure measured by a tail-cuff method in either restrained or anesthetized mice at 9 weeks of age compared with the controls, which was not statistically significant.…”
Section: Apoementioning
confidence: 99%
“…On the second postoperative day, all rats were immunized by subcutaneous administration of 20 mg goat -y-globulin in Freund's complete adjuvant. 6 This was followed on the fifth and eighth postoperative days by intravenous injection of goat •y-globulin with activity directed against rat glomerular basement membrane. Four weeks after induction of nephritis, blood samples and 24-hour urine collections were obtained for determination of blood urea nitrogen, cholesterol, triglyceride, and creatinine in the serum and protein and creatinine in the urine.…”
mentioning
confidence: 99%
“…13 We were then able to demonstrate by video-microscopic visualization of skeletal muscle microvessels in situ that arterioles (20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30) studies in which patients with variant angina were challenged with parasympathetic (methacholine) and sympathetic (epinephrine) agonists. They suggested that enhanced activity of the parasympathetic nervous system was involved in initiating attacks of variant angina.…”
mentioning
confidence: 99%